2002
DOI: 10.1124/jpet.300.2.421
|View full text |Cite
|
Sign up to set email alerts
|

Altered Glutamate Receptor Function during Recovery of Bladder Detrusor-External Urethral Sphincter Coordination in a Rat Model of Spinal Cord Injury

Abstract: Coordination of the bladder detrusor and the external urethral sphincter is a supraspinally controlled reflex that is essential for efficient micturition. This coordination is permanently lost after spinal cord transection but can recover chronically after incomplete spinal cord injury (SCI). As glutamatergic transmission plays a key role in all levels of detrusor-external urethral sphincter coordination, we examined the role of potential alterations in glutamatergic control in its recovery after SCI. Rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 36 publications
3
17
1
Order By: Relevance
“…We found that average days to recovery of spontaneous voiding was approximately 6 days for post-menopausal animals and 5 days for pre-menopausal animals, which was similar to other reports (Nout et al, 2005;Pikov et al, 1998). Although previous work has shown that daily urine volume and/or days to spontaneous voiding are sensitive indicators of lower urinary tract function (Pikov et al, 1998;Pikov and Wrathall, 2002), we did not find significant differences between treatment groups or ages (Fig. 6).…”
Section: Figcontrasting
confidence: 84%
“…We found that average days to recovery of spontaneous voiding was approximately 6 days for post-menopausal animals and 5 days for pre-menopausal animals, which was similar to other reports (Nout et al, 2005;Pikov et al, 1998). Although previous work has shown that daily urine volume and/or days to spontaneous voiding are sensitive indicators of lower urinary tract function (Pikov et al, 1998;Pikov and Wrathall, 2002), we did not find significant differences between treatment groups or ages (Fig. 6).…”
Section: Figcontrasting
confidence: 84%
“…33 Moreover, there are reversible changes in NMDA and AMPA receptor subunit composition and activity during acontractile detrursor and during recovery of voiding reflex in the rat. 34,35 In humans suffering from spasticity and pain, a similar change in the ratio of excitation and inhibition is observed. 36 An acute period of acontractile detrursor is followed by detrusor overactivity.…”
Section: Central Modelssupporting
confidence: 50%
“…Previous work has shown that preservation of white matter is highly correlated with the recovery of hindlimb and lower urinary-tract function in the rodent mid-thoracic spinal cord injury model (Basso, 2000;Fehlings and Tator, 1995;Noble and Wrathall, 1987;Pikov and Wrathall, 2002). Consequently, we evaluated the effect of post-SCI E2 administration on the percentage of white-matter area present in the injury epicenter at 28 days after SCI.…”
Section: Post Spinal Cord Injury Estrogen Administration Increases Whmentioning
confidence: 99%